(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Background: The integration of Electronic Medical Record (EMR) systems has become a cornerstone of modern healthcare management, promising enhanced efficiency, accuracy, and patient care. EMR systems are designed to replace traditional paper-based records with digital solutions that streamline data management and improve accessibility. Despite their potential benefits, the successful implementation of EMR systems is often hampered by several challenges, including complex interfaces, inadequate training for users, and technical issues such as system crashes. Additionally, issues related to system integration, data security, and financial costs can impact the effectiveness of EMR systems. This study aims to explore how these challenges and opportunities manifest in a real-world setting, specifically at Federal Medical Centre (FMC) Abeokuta, to gain insights into the practical implications of EMR adoption on healthcare services. Objective: The objective of this study was to evaluate the challenges and benefits associated with EMR utilization among healthcare professionals at FMC Abeokuta, and to identify factors that promote effective implementation. Method of Analysis: Data were collected through structured questionnaires administered to healthcare professionals involved with EMR systems. Descriptive and inferential statistical methods were employed using SPSS Version 23 to analyze responses related to obstacles, utilization practices, and impacts of EMR systems. Mean scores and standard deviations were calculated to assess the significance of various factors. Results: The analysis revealed that 25% of respondents experienced challenges with EMR interfaces, while 41.67% cited inadequate training as a significant barrier. Technical issues, such as system crashes, affected 29.17% of respondents, and 37.5% reported difficulties integrating paper-based records into EMR. Positive aspects included improved data accuracy, with 50% reporting significant improvements, and enhanced administrative efficiency, with 58.34% noting reduced paperwork. Communication and collaboration were improved for 62.5% of respondents, and 66.67% observed better patient safety and reduced medical errors. Conclusion: The study concluded that while EMR systems offer substantial benefits in terms of data accuracy and operational efficiency, challenges such as system complexity, inadequate training, and technical issues need to be addressed. Investment in user training, enhanced technical support, and effective change management are crucial for optimizing EMR implementation. The findings provide a foundation for improving EMR systems to better serve healthcare professionals and enhance patient care.